Hak Asasi Manusia (HAM) dalam Perspektif Islam dan Barat - Dedi Anton Ritonga; Muhammad Ichsan (Lembaga Pengembangan Kinerja Dosen, 2025)
Human Rights (HAM) are a universal concept that guarantees the freedom and dignity of every individual. From a Western perspective, human rights emerged from a long historical experience marked by oppression, absolutism, and the struggle for individual freedom, thereby emphasizing secular, rational, and individualistic aspects. Meanwhile, in the Islamic perspective, human rights are not only rational and social in nature but also theological, as they originate from divine revelation and are part of human nature (fitrah). Islam views human rights as fundamental rights granted by Allah SWT to all of humanity, which must be respected and protected, with an emphasis on the balance between rights and obligations, as well as between individual freedom and the interests of society. One of the fundamental differences between the two is that human rights in Islam are theocentric, based on the revealed teachings of the Qur'an and Hadith. In contrast, Western-secular human rights are anthropocentric, founded upon philosophical thought as their main foundation.